2011
DOI: 10.1111/j.1464-410x.2011.10532.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of isolated high‐grade prostatic intra‐epithelial neoplasia: proposal of a nomogram for the prediction of cancer detection at saturation re‐biopsy

Abstract: Study Type – Diagnostic (case series) Level of Evidence 4 What's known on the subject? and What does the study add? Multifocality, age, PSA values, and biopsy protocols regarding the predictive value of high grade PIN have been discussed extensively in the literature. Our study developed for the first time a predictive nomogram that could be helpful for patient counselling and to guide the urologist to perform rPBX after an initial diagnosis of isolated HGPIN. OBJECTIVE To evaluate factors that may predict pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
(56 reference statements)
1
13
1
Order By: Relevance
“…Many studies have found that clinical parameters, including a patient's age, various forms of serum PSA measurement and abnormal DRE, do not correlate with the cancer risk associated with HGPIN in subsequent biopsy [5,36]. In the present study, we did not find that a patient's age and the number of repeat biopsy sessions were associated with different cancer risk.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Many studies have found that clinical parameters, including a patient's age, various forms of serum PSA measurement and abnormal DRE, do not correlate with the cancer risk associated with HGPIN in subsequent biopsy [5,36]. In the present study, we did not find that a patient's age and the number of repeat biopsy sessions were associated with different cancer risk.…”
Section: Discussioncontrasting
confidence: 79%
“…The mean follow‐up in the present study is 27.4 months and almost half of the patients had at least two follow‐up biopsies. Longer follow‐up detects not only concomitant PCa but also new PCa that develops from HGPIN; therefore the incidence of PCa detection increases with the number of repeat biopsies and follow‐up duration [35,36]. As Lefkowitz et al .…”
Section: Discussionmentioning
confidence: 99%
“…This recommendation is based on quadrant and sextant biopsies, and may not apply for extended biopsy sampling. (Table 10) Follow‐up biopsy is suggested within one year, especially in those with multifocal PIN or those in whom PIN is detected with less than initial 12‐core biopsy 117,124,125 . If all procedures fail to identify coexistent carcinoma, close surveillance and follow‐up are indicated.…”
Section: Clinical Significance Of Pinmentioning
confidence: 99%
“…HGPIN is often found in close proximity to invasive adenocarcinomas and it shares a number of defining morphological features with invasive adenocarcinomas such as nuclear and nucleolar enlargement [11,12]. Furthermore, the presence of extensive HGPIN on prostate needle biopsy is associated with an elevated risk of cancer on subsequent biopsies [1316]; invasive ‘microcarcinomas’ at times appear to arise from HGPIN lesions [17]; HGPIN and adenocarcinoma share a number of molecular features [11,1820]; and HGPIN lesions share a number of somatic genetic and epigenetic alterations with invasive prostatic adenocarcinomas [4,6,11,2127]. It is important to note, however, that most of the previous studies evaluating somatic DNA alterations in HGPIN and adjacent cancers used low-resolution and mostly fluorescence in situ hybridization (FISH)-based approaches, which although suggestive of a common clonal relationship between HGPIN and invasive carcinomas, did not allow a definitive evaluation of clonal ancestry.…”
Section: Introductionmentioning
confidence: 99%